2000
DOI: 10.1530/eje.0.1420549
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of bone turnover in children with GH deficiency treated with GH until final height

Abstract: Objective: To examine the dynamics of bone turnover in children with growth hormone deficiency (GHD) during long-term treatment. Design: We longitudinally measured growth velocity and serum concentrations of osteocalcin (OC), carboxyterminal propeptide of type I procollagen (PICP), and cross-linked carboxyterminal telopeptide of type I collagen (ICTP) in 24 patients with GHD during long-term GH treatment until final height (age: 7.7 Ϯ 0.7 and 16.9 Ϯ 0.5 years at baseline and at final height respectively). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 46 publications
(66 reference statements)
1
28
1
Order By: Relevance
“…Twenty-four months after cessation of GH treatment, lumbar bone mass had declined in patients but not in controls. These results suggest that in young adults with GHD, GH replacement may be needed to support adequate bone mass accumulation in order to maintain bone mass in adult life (21)(22)(23). Furthermore, it seems likely that adolescents with severe GHD may not have achieved their peak bone mass at adult height, when GH treatment is often discontinued, and that GH may play an important role in the acquisition and maintenance of bone mass during this particular period of bone consolidation (3,(24)(25)(26).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Twenty-four months after cessation of GH treatment, lumbar bone mass had declined in patients but not in controls. These results suggest that in young adults with GHD, GH replacement may be needed to support adequate bone mass accumulation in order to maintain bone mass in adult life (21)(22)(23). Furthermore, it seems likely that adolescents with severe GHD may not have achieved their peak bone mass at adult height, when GH treatment is often discontinued, and that GH may play an important role in the acquisition and maintenance of bone mass during this particular period of bone consolidation (3,(24)(25)(26).…”
Section: Introductionmentioning
confidence: 90%
“…However, the timing of acquisition of peak bone mass in young adults with GHD is not well researched. In a study of 16 adolescent patients (aged 15-19 years) with isolated GHD, lumbar BMD area (bone mineral content (BMC) corrected for vertebral surface area) and lumbar BMD volume (BMC corrected for vertebral volume) were below the normal mean, and mean values of peak BMD were reduced in patients compared with controls (21). Twenty-four months after cessation of GH treatment, lumbar bone mass had declined in patients but not in controls.…”
Section: Introductionmentioning
confidence: 98%
“…Studies in children with GH deficiency have shown that GH deficiency-associated reduced bone turnover is reversed with GH therapy. 27 Because the foundation for skeletal health is established in childhood, prevention of decreased bone mineral density begins by optimizing gains in bone mineral acquisition throughout childhood. Although bone health among children after HCT has not been well studied, one report shows that the effect of GH and bisphosphonate therapy on bone mineral density resulted in an improvement in bone mineral density among those treated with GH and bisphosphonate compared to those who received GH without bisphosphonate.…”
Section: Growthmentioning
confidence: 99%
“…In children and adolescents with GHD, BMD assessed by DEXA and bone turnover are significantly reduced (40), reflecting decreased bone modeling and remodeling (41), because of delayed bone maturation or absence of GH anabolic activity (42).…”
Section: Gh Deficiency (Ghd)mentioning
confidence: 99%